Omega-conotoxin-sensitive and -resistant transmitter release from the chick ciliary presynaptic terminal. - Yawo, H (1994)
1. Synaptically evoked responses to stimulation of the oculomotor nerve were recorded from the ciliary nerve in chick embryos. The postsynaptic currents in response to presynaptic stimulation (EPSCs) were also recorded under whole-cell voltage clamp of the ciliary cell. 2. The ciliary nerve response was dependent on the extracellular Ca2+ concentration ([Ca2+]o). omega-Conotoxin GVIA (omega-CgTX, 100 nM) increased the [Ca2+]o necessary to evoke the half-maximal response by a factor of 1.7 without changing the slope of [Ca2+]o dependence. Dihydropyridine (DHP) derivatives, nifedipine or Bay K 8644, did not affect the [Ca2+]o sensitivity of ciliary nerve response. 3. The EPSC was usually preceded by the capacitive coupling response of the presynaptic action potential. In some records, the EPSCs were also preceded by the electrical coupling responses which were the mirror images of the presynaptic action potentials. The current-voltage relation of the EPSCs showed inward rectification. 4. The EPSC was potentiated by 4-aminopyridine (4-AP) as a result of prolongation of the falling phase of presynaptic action potential. In the presence of high [Ca2+]o and 4-AP, a small fraction of EPSC was resistant to omega-CgTX. 5. The resting potential of the presynaptic terminal was changed from -69 to -57 mV by increasing [K+]o from 1 to 10 mM. The same procedure decreased the omega-CgTX-resistant EPSC by 30%, whereas the omega-CgTX-untreated EPSC in low-Ca2+ saline was not affected by the change in [K+]o. 6. The nerve-evoked increase in intracellular Ca2+ was recorded from the presynaptic terminal (delta[Ca2+]pre). The delta[Ca2+]pre was larger in a solution containing 10 mM Ca2+ and 1 mM K+ after treating with omega-CgTX than in a solution containing 2 mM Ca2+ and 16 mM Mg2+ before treating with omega-CgTX. The EPSC was, in contrast, smaller in the 10 mM Ca(2+)-1 mM K+ solution after omega-CgTX treatment than in the 2 mM Ca(2+)-16 mM Mg2+ solution before omega-CgTX treatment. 7. Similarly, the EPSC was smaller in the 10 mM Ca(2+)-1 mM K+ solution containing 5 microM La3+ than in the 2 mM Ca(2+)-16 mM Mg2+ solution, whereas the delta [Ca2+]pre was larger in the 10 mM Ca(2+)-1 mM K+ solution containing 5 micrograms La3+ than in the 2 mM Ca(2+)-16 mM Mg2+ solution. 8. It is concluded that the omega-CgTX-sensitive Ca2+ conductance of the presynaptic terminal is the principal source of Ca2+ involved in transmitter release.(ABSTRACT TRUNCATED AT 400 WORDS)